Targeting the N-cadherin/β-catenin axis with MSAB reverses malignant phenotypes in blast crisis of CML - Zhou, Yingying; Jian, Songqin; Lu, Lijun; Li, Xiaofang; Qiu, Ruyi (Frontiers in Oncology, 2025)
IntroductionThe molecular mechanisms underlying chronic myeloid leukemia (CML) progression from chronic phase (CP) to blast crisis (BC) remain incompletely understood. This study aimed to identify progression-specific genes and elucidate the role of N-cadherin (CDH2) in BC transformation.MethodsWe analyzed the GSE4170 dataset to identify differentially expressed genes (DEGs) across CML phases. Functional annotations were performed via GSEA, GO, and KEGG analyses. The role of N-cadherin was validated using in vitro (KU812 cell line) and in vivo (nude mouse xenograft) models. The β-catenin inhibitor MSAB was employed for mechanistic studies.ResultsTranscriptomic analysis identified 1,294 DEGs during CML progression, with 41 "progression-specific" genes showing consistent expression trends. Among these, N-cadherin was significantly upregulated in BC patient samples. Overexpression of N-cadherin in KU812 cells promoted cell cycle entry, accelerated tumor growth in vivo, and suppressed the expression of granulocyte surface differentiation antigens. MSAB treatment effectively reversed these malignant phenotypes. Furthermore, CDH2 mRNA was notably upregulated in advanced-phase samples compared to chronic-phase samples.DiscussionOur findings elucidate the role of CDH2 in CML progression through activation of the Wnt/β-catenin signaling pathway. Targeting the N-cadherin/β-catenin axis with MSAB may represent a novel therapeutic strategy for BC-CML.